UTanggap Beberapa Dosis Pupuk Organik Kascing Terhadap Pertumbuhan Dan Hasil Tanaman Sawi (Brassica juncea L.) Yang Berbeda Varietas - Teguh Yuda Pratama; Nurmayulis Nurmayulis; Imas Rohmawati (Faculty of Agriculture, Pattimura University, 2018)
The research was aimed to know the effect of dose of organic fertilizer to growth and yield varieties of mustard (Brassica juncea L.). The method used was a randomized block design a Randomized Completely Block Design with 2 factors. The first factor was the organic fertilizer, namely (P) and the second factor was the variety. The first factors was the organic vermicompost, which consists of 4 levels, namely: P0 = 0 g / plant, P1 = 30 g / plant, P2 = 60 g / plant, P3 = 90 g / plant the second factor was varieties, which consists of three levels, namely: V1 = Tosakan varieties, V2 = Kumala varieties, V3 = Sri Tanjung varieties. Thus there was 12 combinations of treatment, each treatment was repeated three times, in order to get 36 experimental unit. Parameters measured were plant height, number of leaves, plant fresh weight, plant dry weight, root dry weight. The results of this research showed that vermicompost fertilizer showed significant effect on the observation parameters plant height, root length, fresh weight of plant, plant dry weight, root dry weight. Vermicompost fertilizer dose of 60 g / plant give the best average results in almost all variables observation (plant height 18,6 g, fresh weight of plant 10,3 g, plant dry weight 1,3 g and root dry weight 0,4 g. Kumala varieties gave the highest rates in the observation parameters number of leaves 7,2 sheet and fresh weight of plant 10,0 g. The interaction of both treatment showed no real effect on all parameters of observation.